Gender Role Attitudes and Depressive Symptoms of the Mother-Daughter Dyad in Korea* - Ho, Jeong Hwa (Journal of Asian Sociology, 2020)
Gender role attitudes are a lens through which people make sense of life. Several studies have examined the psychological consequences of egalitarian gender role attitudes and found significant associations. Gender socialization and ideologies are practiced daily in the family. However, little is known about how family members' gender role attitudes influence the psychological wellbeing of other members of their family. This study examined interactive associations between the gender role attitudes and depressive symptoms of young daughters (aged 19-35) and their mothers (aged 40-68) in Korea. Actor-partner interdependence model analysis revealed significant within-dyad nonindependence. Daughters' egalitarian gender role attitudes were related to lesser depressive symptoms in themselves, while egalitarian outlooks of mothers predicted greater depressive symptoms in daughters. Daughters' egalitarian gender role attitudes, though not mothers' own attitudes, were associated with lesser depressive symptoms in mothers. This suggests that the egalitarian gender ideology does not directly result in better wellbeing within the mother-daughter dyad. The relationship is complicated within the context of sociocultural settings.
Keywords: Depressive feeling; Gender role attitudes; Korea; Mother-daughter dyad